Integrin αβ–Targeted Dynamic Contrast–Enhanced Magnetic Resonance Imaging Using a Gadolinium-Loaded Polyethylene Gycol–Dendrimer–Cyclic RGD Conjugate to Evaluate Tumor Angiogenesis and to Assess Early Antiangiogenic Treatment Response in a Mouse Xenograft Tumor Model - Wei-Tsung Chen; Tiffany Ting Fang Shih; Ran-Chou Chen; Shin-Yang Tu; Hsieh Wen-Yuen; Pang-Chyr Yang (Molecular Imaging)
The purpose of this study was to validate an integrin α v β 3 –targeted magnetic resonance contrast agent, PEG-G3-(Gd-DTPA) 6 -(cRGD-DTPA) 2 , for its ability to detect tumor angiogenesis and assess early response to antiangiogenic therapy using dynamic contrast–enhanced (DCE) magnetic resonance imaging (MRI). Integrin α v β 3 –positive U87 cells and control groups were incubated with fluorescein-labeled cRGD-conjugated dendrimer, and the cellular attachment of the dendrimer was observed. DCE MRI was performed on mice bearing KB xenograft tumors using either PEG-G3-(Gd-DTPA) 6 -(cRGD-DTPA) 2 or PEG-G3-(Gd-DTPA) 6 -(cRAD-DTPA) 2 . DCE MRI was also performed 2 hours after anti–integrin α v β 3 monoclonal antibody treatment and after bevacizumab treatment on days 3 and 6t. Using DCE MRI, the 30-minute contrast washout percentage was significantly lower in the cRGD-conjugate injection groups. The enhancement patterns were different between the two contrast injection groups. In the antiangiogenic therapy groups, a rapid increase in 30-minute contrast washout percentage was observed in both the LM609 and bevacizumab treatment groups, and this occurred before there was an observable decrease in tumor size. The integrin α v β 3 targeting ability of PEG-G3-(Gd-DTPA) 6 -(cRGD-DTPA) 2 in vitro and in vivo was demonstrated. The 30-minute contrast washout percentage is a useful parameter for examining tumor angiogenesis and for the early assessment of antiangiogenic treatment response.